Integration of Walisongo’s Da’wah Spirit with Science in Indonesian National Qualification Framework Based Curriculum - Agus Zaenul Fitri; Muntahibun Nafis; Fathul Mujib (UIN Maulana Malik Ibrahim Malang, 2019)
This research aims to explain the views of policymakers, the concept of integration in scientific development, and the strategy of integrating da’wah spirit of Walisongo with science in the Indonesian National Qualification Frameworks (KKNI) based curriculum. The results of this study indicate that: (1) stakeholders states that spirit of Walisongo’s dakwah has been used as values in science development by some academics, although it has not been fully understood because some academics still see it as a myth. The spirit of institutional management should match with the institution name itself, otherwise, there will be management error; (2) the concept of integration in KKNI-based curriculum in three institutions has similarities in general. However, there are distinctive characteristics in developing scientific knowledge based on the vision and core values of each institution; (3) the strategy of integrating the spirit of Walisongo is reflected in evaluating aspects: (a) institutions, by building interconnections, tag line or owner’s quote, piety bureaucracy (clean and clear), (b) human resources development, and (c) academic integration through Islamic subject with science and technology, halal laboratories, and Islamic law.Penelitian ini bertujuan menjelaskan pandangan pengambil kebijakan, konsep integrasi dalam pengembangan ilmiah, dan strategi mengintegrasikan semangat dakwah Walisongo dengan ilmu pengetahuan dalam kurikulum berbasis Kerangka Kualifikasi Nasional Indonesia (KKNI). Hasil penelitian ini menunjukkan: (1) pemangku kepentingan berpendapat bahwa semangat dakwah Walisongo telah digunakan sebagai nilai dalam pengembangan ilmu pengetahuan beberapa akademisi, tetapi belum sepenuhnya dipahami karena masih ada beberapa warga akademik yang menganggapnya sebagai mitos. Semangat manajemen kelembagaan harus sesuai dengan nama lembaga tersebut, jika tidak maka ada kesalahan manajemen, (2) konsep integrasi dalam kurikulum berbasis KKNI di tiga lembaga memiliki kesamaan pada umumnya tetapi memiliki karakteristik khusus dalam mengembangkan pengetahuan ilmiah berdasarkan visi dan nilai-nilai inti lembaga. (3) Strategi memadukan semangat Walisongo tercermin dari mengevaluasi aspek-aspek yaitu: a) institusi dengan cara membangun interkoneksi, slogan atau falsafah pendirinya, birokrasi kesalehan (bersih dan jelas), b) pengembangan sumber daya manusia, dan c) integrasi akademik melalui mata pelajaran Islam dengan sains dan teknologi, laboratorium halal, dan hukum Islam.